Targeted nanozyme-enabled treatment of cardiovascular diseases - Lin Liu; Jie Lv; Xiuxiu Wang; Xiao Huang; Chenchen Zhang; Qingqing Pan; Wei Yan; Zhen Qin (Acta Materia Medica)
Cardiovascular diseases (CVDs) pose a significant threat to human health due to the high mortality and morbidity rates. Traditional drugs often have limited efficacy due to inherent constraints, such as low bioavailability and notable side effects. As a highly regarded therapeutic strategy, nanotechnology offers new perspectives and means for treating CVDs. Nanozyme-based targeted therapeutic drugs specifically address the biological processes in areas affected by CVDs, thereby achieving precise treatment. Compared to traditional drugs, targeted nanozymes offer advantages, such as high efficiency, specificity, controllability, and fewer side effects, showing great efficacy in treating CVDs. This paper first explores the design strategies and mechanisms of nanozyme-based targeted therapy, then introduces its application in key CVDs, such as ischemic stroke, myocardial infarction, and coronary heart disease. Finally, the paper discusses the challenges of introducing targeted nanozymes into clinical applications and the future development prospects in the treatment of CVDs.